2008
DOI: 10.1097/01.phh.0000338371.53242.0e
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Associations Between Ambient Ozone and Asthma-Related Emergency Department Visits Using Case-Crossover Analysis

Abstract: Traditional environmental public health surveillance consists of separately measuring hazards, exposures, and health outcomes. The Environmental Public Health Tracking (EPHT) Network seeks to accrue additional information by linking hazard or exposure data to health outcomes data. A natural progression is to consider tracking the "link" itself, that is, to track the association between an environmental hazard and a health outcome. The Maine EPHT Program conducted a case-crossover analysis to measure associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…However, some studies have reported positive associations among both children and adults, with no evidence of effect measure modification by age (Ko et al 2007; Mar and Koenig 2009; Paulu and Smith 2008). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies have reported positive associations among both children and adults, with no evidence of effect measure modification by age (Ko et al 2007; Mar and Koenig 2009; Paulu and Smith 2008). …”
Section: Resultsmentioning
confidence: 99%
“…For example, there is evidence for higher relative risk estimates in females compared with males in studies of chronic obstructive pulmonary disease HAs and ED visits (Arbex et al 2009; Wong et al 2009). However, in studies of asthma ED visits, differences between males and females were observed by age: Larger relative risk estimates were reported for males 2–14 years and females 15–34 years of age, with no evidence of any sex differences in those 35–64 years of age (Paulu and Smith 2008). These results are consistent with Thaller et al (2008), who found evidence of decreased lung function in females compared with males 16–27 years of age.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, a majority of the articles focused on outdoor air pollution and accounted for 37% of publications in this category. The articles that demonstrated a specific adverse health outcome or health effect associated with outdoor air pollution is as follows: asthma (38%), 14,19,42,43,48,55,66,69 acute myocardial infarction (19%), 14,57,58,69 cancer (10%), 21,34 adverse birth or reproductive outcomes (10%), 68,75 other respiratory diseases (10%), 42,56 and other cardiovascular disease outcomes (10%). 61,68 Nine percent of the articles in the Science and Research category focused on water contaminants.…”
Section: Resultsmentioning
confidence: 99%
“…Tracking Program partners have evaluated the association between ambient levels of ozone and PM 2.5 and traffic density with short-term asthma-related health outcomes (Babin et al, 2007; Paulu and Smith, 2008; Wilhelm et al, 2008). These analyses identified age- and sex- specific populations at risk as well as differences in the exacerbation of asthma-related outcomes particular to the exposure scenario.…”
Section: Tracking: the Early Yearsmentioning
confidence: 99%
“…It's unclear how modeling decisions, data characteristics, outcome sparseness, strength of association, and spatial autocorrelation may affect results of this and similar studies. Similarly, the case-crossover method is used frequently to analyze the effects of air pollution and heat, however, we need to understand the effects of decisions such as referent period selection and estimation of air pollution and meteorological conditions on study results (Paulu and Smith, 2008). Sophisticated modeling approaches for air pollution, such as kriging or land use-based regression modeling, better characterize spatial and temporal variability in air pollution (Jerrett et al, 2005; Wilhelm et al, 2008), however, they require expertise and resources that are not always available within a single institution or agency.…”
Section: Challenges Remainmentioning
confidence: 99%